Bleeding and Infection With External Ventricular Drainage: A Systematic Review in Comparison With Adjudicated Adverse Events in the Ongoing Clot Lysis Evaluating Accelerated Resolution of Intraventricular Hemorrhage Phase III (CLEAR-III IHV) Trial. Issue 3 (March 2015) - Dey, Mahua; Stadnik, Agnieszka; Riad, Fady; Zhang, Lingjiao; McBee, Nichol; Kase, Carlos; Carhuapoma, J. Ricardo; Ram, Malathi; Lane, Karen; Ostapkovich, Noeleen; Aldrich, Francois; Aldrich, Charlene; et al.
Abstract : BACKGROUND: Retrospective series report varied rates of bleeding and infection with external ventricular drainage (EVD). There have been no prospective studies of these risks with systematic surveillance, threshold definitions, or independent adjudication. OBJECTIVE: To analyze the rate of complications in the ongoing Clot Lysis: Evaluating Accelerated Resolution of Intraventricular Hemorrhage Phase III (CLEAR III) trial, providing a comparison with a systematic review of complications of EVD in the literature. METHODS: Patients were prospectively enrolled in the CLEAR III trial after placement of an EVD for obstructive intraventricular hemorrhage and randomized to receive recombinant tissue-type plasminogen activator or placebo. We counted any detected new hemorrhage (catheter tract hemorrhage or any other distant hemorrhage) on computed tomography scan within 30 days from the randomization. Meta-analysis of published series of EVD placement was compiled with STATA software. RESULTS: Growing or unstable hemorrhage was reported as a cause of exclusion from the trial in 74 of 5707 cases (1.3%) screened for CLEAR III. The first 250 patients enrolled have completed adjudication of adverse events. Forty-two subjects (16.8%) experienced ≥1 new bleeds or expansions, and 6 of 250 subjects (2.4%) suffered symptomatic hemorrhages. Eleven cases (4.4%) had culture-proven bacterial meningitis or ventriculitis. CONCLUSION: Risks of bleeding and infection in the ongoing CLEAR III trial are comparable to those previously reported in EVD case series. In the present study, rates of new bleeds and bacterial meningitis/ventriculitis are very low despite multiple daily injections, blood in the ventricles, the use of thrombolysis in half the cases, and generalization to >60 trial sites. ABBREVIATIONS: CI, confidence interval CLEAR, Clot Lysis: Evaluating Accelerated Resolution of Intraventricular Hemorrhage EVD, external ventricular drainage ICH, intracerebral hemorrhage IVH, intraventricular hemorrhage rtPA, recombinant tissue-type plasminogen activator